Síntese de ftalocianinas funcionalizadas com grupos sulfonamida - Carvalho, Eliana Filipa Anjos (2009)
O trabalho descrito nesta dissertação envolveu a síntese e a caracterização estrutural de novas ftalocianinas contendo grupos sulfonamida com potencial interesse para uso em terapia fotodinâmica, catálise ou limite óptico. Na primeira parte experimental, são abordados as reacções que envolvem a funcionalização de ftalonitrilos com grupos sulfonamida e posterior condensação dos mesmos em ftalocianinas simétricas. Na segunda parte experimental, é abordado o estudo de uma rota sintética de ftalocianinas assimétricas, do tipo A3B, para posterior clorossulfonação e conversão em sulfonamidas. A estrutura dos compostos sintetizados foi estabelecida com recurso a diversas técnicas espectroscópicas, nomeadamente ressonância magnética nuclear (RMN de 1H e RMN de 13C), espectrometria de massa e UV-vis. ABSTRACT: The work in this dissertation involves the synthesis and structural characterization of new phthalocyanines containing sulfonamide groups. These compounds have potential application in photodynamic therapy, in catalysis or in optical limiting. In the first experimental part, it is described the reactions that involve the functionalization of phthalonitriles and their condensation into symmetrical phthalocyanines. In the second part, it is described the study of a synthetic route to substituted phthalocyanines of the A3B type. These were prepared via cross-condensation of two phthalonitriles, followed by chlorosulfonation. Reaction of the chlorosulfonyl groups with amines resulted in the formation of the expected sulfonamide groups. The structural characterization of the synthesized compounds was made by using several spectroscopic techniques, namely nuclear magnetic resonance (1H NMR and 13C NMR), mass spectrometry and UV-visible.